Abdullah Ahmad Badawi : satu tahun di Putrajaya : [kertas kerja seminar] - Pandian, Sivamurugan (Cheras, Kuala Lumpur: Utusan Publications & Distributors, 2006)
One year performance of Abdullah Ahmad Badawi as prime minister of Malaysia; seminar papers.
Includes bibliographical references (p. 184-192).
In Malay.
Keywords: Abdullah bin Haji Ahmad Badawi,, -- Datuk,, -- 1939-; Malaysia -- Politics and government